ACCESSIBILITY FOR PERSONS WITH DISABILITIES IN BUILT ENVIRONMENT OF URBAN AREA: CASE STUDY OF GEORGE TOWN, PENANG - Ali Wazani, Ikhwan; Mohamad, Diana; Jaafar, Mastura (PLANNING MALAYSIA, 2021)
Persons with Disabilities (PwD) confront several challenges that hinder them from fully exercising their rights and participating in social, professional, and cultural activities when it comes to accessing built environment. This paper is to investigate the accessibility challenges that PwD face in George Town, Penang. The questionnaire survey techniques employed was to obtain data from a group of PwD. The questionnaire was conducted on wheelchair users, the walking impaired, the visually impaired, and the hearing impaired in George Town areas. Most PwD three key challenges, such as narrow sidewalks, uneven sidewalk surfaces, barriers on sidewalks and dangerous drop curbs. Accessibility facilities in George Town still need to be improved to make it easier for PwD to get around. The findings and recommendations in this study would assist in improving current access to a built environment so that PwD may visit the George Town areas easily and safely.